Diels-Alder reaction mechanisms of substituted chiral anthracene: A theoretical study based on the reaction force and reaction electronic flux (2020)
Quantum chemical calculations were used to study the mechanism of Diels-Alder reactions involving chiral anthracenes as dienes and a series of dienophiles. The reaction force analysis was employed to obtain a detailed scrutiny of the reaction mechanisms, it has been found that thermodynamics and kinetics of the reactions are quite consistent: the lower the activation energy, the lower the reaction energy, thus following the Bell-Evans-Polanyi principle. It has been found that activation energies are mostly due to structural rearrangements that in most cases represented more than 70% of the activation energy. Electronic activity mostly due to changes in σ and π bonding were revealed by the reaction electronic flux (REF), this property helps identify whether changes on σ or π bonding drive the reaction. Additionally, new global indexes describing the behavior of the electronic activity were introduced and then used to classify the reactions in terms of the spontaneity of their electronic activity. Local natural bond order electronic population analysis was used to check consistency with global REF through the characterization of specific changes in the electronic density that might be responsible for the activity already detected by the REF. Results show that reactions involving acetoxy lactones are driven by spontaneous electronic activity coming from bond forming/strengthening processes; in the case of maleic anhydrides and maleimides it appears that both spontaneous and non-spontaneous electronic activity are quite active in driving the reactions. © 2020 Wiley Periodicals LLC